Nickel‐Photoredox‐Catalyzed Synthesis of sp2−sp3 Fragments and the Impact of Bicycloalkane Isosteric Replacement on Their Physical‐Chemical Properties. Issue 4 (6th March 2023) - Lefebvre, Quentin; Bocu, Mina; Giorgiutti, Christophe; Fessard, Thomas C.
Abstract: Bicycloalkanes are well‐known isosteres of alkynes and aromatic rings and their use in the field of medicinal chemistry and drug discovery has been on the rise in the past ten years. Herein, we report the modular and practical synthesis of bicycloalkane‐containing fragments using nickel‐photoredox catalysis. The comparison of their relevant physical‐chemical properties with their aromatic counterparts shows a substantial improvement in Log P and aqueous solubility for bicyclo[1.1.1]pentane derivatives, but not for bicyclo[2.2.2]octane derivatives. Abstract :